Changes in Indonesian Export Commodities from Oil and Gas to Non-Oil and Gas, 1979-1987 - Putri, Erike Tesy Cahaya; Rinardi, Haryono (Diponegoro University, 2024)
Through four stages in the historical methods, this article examines the problem regarding the relationship between the oil and gas crisis in 1981 and government’s effort in developing non-oil and gas export using an economics approach method. Indonesia's economic condition in 1979-1980 was marked by the triumph of oil revenues due to the increase in international oil prices, which reached US32/barrel. Indonesia, as an exporter country, takes advantage of this condition by doubling its oil export volume. Two years of running, high oil prices have indirectly caused Western industrial countries to feel burdened and unabled to buy oil supplies; therefore, there was an overflow of oil supply in the international market. The government carried out a non-migration export campaign marked by the issuance of PP No. 1 of 1982, concerning the 1982 Export Policy Package. After the campaign, the value of non-oil and gas exports did not increase, as evidenced by a decrease of 0,87% in 1983, from US3.928 million to US3.894 million. Therefore, the government formulated regulations for non-oil and gas exports with the Policy Package of May 6, 1986, accompanied by devaluation in the same year. Through these efforts, the value of non-oil and gas exports increased significantly, reaching US9.502 million in 1987, or an increase of 41% from 1986. Remarkably, in 1987, the value of non-oil and gas exports for the first time exceeded oil and gas exports, with US661 million deviations